2001
DOI: 10.1007/s007920000170
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of two pectate lyase genes from the marine Antarctic bacterium Pseudoalteromonas haloplanktis strain ANT/505 and characterization of the enzymes

Abstract: A marine Antarctic psychrotolerant bacterium (strain ANT/505), isolated from sea ice-covered surface water from the Southern Ocean, showed pectinolytic activity on citrus pectin agar. The sequencing of the 16S rRNA of isolate ANT/505 indicates a taxonomic affiliation to Pseudoalteromonas haloplanktis . The supernatant of this strain showed three different pectinolytic activities after growth on citrus pectin. By activity screening of a genomic DNA library of isolate ANT/505 in Escherichia coli , two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 28 publications
6
38
0
1
Order By: Relevance
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 89%
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 89%
“…A marine Antarctic, psychrotrophic bacterium (Pseudoalteromonas haloplanktis, strain ANT/505), isolated from sea ice covered surface water from the Southern Ocean, showed pectinolytic activity on citrus pectin agar. Isolated enzymes (pelA and pelB) from this strain represented the first pectate lyase isolated and characterized from a cold-adapted marine bacterium (Truong et al, 2001).…”
Section: Identification Of Psychrophilic Strainmentioning
confidence: 99%
“…SC-G and SC-H and also from two yeast strains isolated from grapes (Cabeza et al, 2009). Pectate lyase genes have been cloned and the enzyme overexpressed from the marine antarctic bacterium Pseudomonas haloplanktis strain ANT/505 was pectinolytic toward citrus pectin agar (Truong et al, 2001), with optimal activity at 30 • C and a 2-min half-life at 40 • C. The psychrophilic yeast Mrakia frigida also produces a cold-active pectate lyase with optimal activity at 30 • C (Margesin et al, 2005). Birgisson et al (2003) also found eight strains of cold-adapted yeasts, including Cryptococcus and Cytofilobasidium spp.…”
Section: Enzymes From Cold-adapted Organismsmentioning
confidence: 99%